Anemia in Pediatric Kidney Transplant Recipients—Etiologies and Management - Kouri, Anne; Balani, Shanthi; Kizilbash, Sarah (Frontiers in Pediatrics, 2022)
Posttransplant anemia (PTA) is a common complication of pediatric kidney transplantation, with a prevalence ranging from 22-to 85%. PTA is categorized as early (within 6 months posttransplant) and late (> 6 months posttransplant). Early PTA is typically associated with surgical blood losses and iron deficiency. Late PTA primarily results from graft dysfunction; however, iron deficiency, drug toxicity, and posttransplant inflammation also play a role. PTA is more severe compared with the anemia in glomerular-filtration-rate matched patients with native chronic kidney disease. Treatment of PTA is directed towards the underlying cause. Erythropoiesis stimulating agents (ESA) are effective; however, their use is limited in the transplant setting. Timely diagnosis and treatment of PTA are vital to prevent long-term adverse outcomes in pediatric transplant recipients.